The influences of the flipgrid application on EFL learners’ speaking anxiety in a high school in the Mekong delta : - Trần, Thị Bạch Tuyết (Trường Đại học Cần Thơ, 2020)
Research on the use of Flipgrid in the language classrooms has focused on the effects of online video-mediated communication tool, learners‟ attitudes and perceptions; nonetheless, not much research has recently been conducted about the influences of the Flipgrid app on EFL learners‟ speaking anxiety. Therefore, this research aimed at investigating whether or not Flipgrid helps the EFL high school learners reduce their speaking anxiety and determine EFL learners‟ attitudes towards the use of Flipgrid in learning English speaking. The research followed a mixed-method design in which a combination of a quasi-experimental study and a descriptive study was conducted with the participation of 60 EFL tenth-grade learners in a high school context of the Mekong Delta. Three research instruments namely the modified Foreign Language Classroom Anxiety Scale (FLCAS), questionnaire, and semi-structured interviews were employed in this study. The quantitative data were entered into SPSS version 20.0 for data analysis. The findings divulged a decrease in EFL high school learners‟ level of speaking anxiety after they had experienced Flipgrid for speaking. Moreover, the majority of EFL learners also showed their high positive attitudes towards the use of Flipgrid in learning English speaking and expected that Flipgrid should be employed frequently to make learning English speaking more motivating. The numerous implications for the pedagogical application of Flipgrid in learning English speaking with regard to reducing the EFL high school learners‟ speaking anxiety were also presented in this current inquiry.